O processo de internacionalização do setor siderúrgico brasileiro: um estudo das empresas CSN, Usiminas e Gerdau - Oliveira, Geovana Canova de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Trade liberalization was importante after World War II in order to boost the global economy. However, the tariff trad barriers have been replaced by non-tariff trade barriers, making the trade even harder. This scenario forced the brazilian companies to seek new entry strategies in the international market, wich occured through internationalization via Foreign Direct Investment (FDI). The aim of this dissertation it to analyze the dynamics of brazilian steel companies’ internationalization process, focusing on CSN, Usiminas and Gerdau. For That, a estudy about internationalization theories, Foreign Direct Investments and, tariff negotiations was done, as well as an analysis of trade between Brazil and its main partners in order to identify whether there is a trade-off between the importer’s level of development and steel goods’ degree of value added. Support was sought in specialized literature, in consultation with the economic and financial press and, in industry reports issued by the appropriate authorities

A liberalização comercial mostrou-se importante após a 2ª Guerra Mundial com o intuito de dinamizar as economias após o conflito. No entanto, as barreiras comerciais tarifárias foram substituídas pelas barreiras não tarifárias, dificultando o comércio. Este cenário obrigou as empresas brasileiras a buscarem novas estratégias de entrada no mercado internacional, o que ocorreu por meio da internacionalização via Investimento Direto Estrangeiro (IDE). O objetivo desta monografia é analisar a dinâmica do processo de internacionalização das empresas brasileiras do setor siderúrgico, com foco na CSN, Usiminas e Gerdau. Para tanto, faz-se um estudo das teorias de internacionalização, dos Investimentos Diretos Estrangeiros (IDE’s) e das negociações tarifárias entre os países, além de uma análise acerca do comércio entre o Brasil e seus principais parceiros com o objetivo de identificar se existe um trade-off entre o nível de desenvolvimento do importador e o grau de agregação de valor do bem siderúrgico. Buscou-se apoio em literatura especializada, em consulta à imprensa econômico-financeira e, em relatórios do setor divulgados pelas autoridades competentes
The internationalization process of the Brazilian steel sector: a study of CSN, Usiminas and Gerdau
Keywords: Tariffs; Trade; Internationalization; Tarfias; Comércio; Internacionalização; Setor siderúrgico; Trade-off